Review and benchmark study on the analysis of low-velocity impact on composite laminates. (April 2018) - Bogenfeld, Raffael; Kreikemeier, Janko; Wille, Tobias
Abstract: For the analysis of low-velocity impact damage, many analytical and numerical models were developed by various authors. These models range from simple approaches with a single degree of freedom up to finite element models on micro-scale. The prediction of delamination, fiber failure, and inter-fiber damage, as well as a physically sound kinematic behavior, are usually the objectives of these simulations. However, achieving satisfactory results requires massive computation and modeling efforts. In the present paper, we review the capability to capture impact damage on the coupon and the structural level. For this purpose, a large compendium of analytical and numerical analysis methods from various authors is considered. Based on existing works, six representative modeling approaches of different abstraction scales are derived and considered on a qualitative and quantitative benchmark study. We analyze all models regarding their advantages and deficiencies. With two experimental coupon impacts, all approaches are tested on their predictive capabilities on the coupon level. The applicability of these methods on the structural level is evaluated according to the benchmark results. Modeling approaches included in the benchmark range from high-fidelity models on meso-scale, macro-scale shell models, and analytical estimations. The focus is put on stacked layer models with solid or shell elements and various cohesive zone approaches. With this paper, we also present guidelines for impact analysis strategies on the structural level. These guidelines aim for a good balance between accuracy and computation effort and involve various simplifications of impact scenarios. In this regard, the range of low-velocity has to be monitored. The energy distribution over the eigenmodes of the impact system suitably indicates the limit of low-velocity impact. Highlights: A comprehensive review of impact analysis methods on different abstraction scales Quantitative and qualitative benchmark of numerical and analytical methods A guideline for choosing an appropriate impact analysis approach is established. Strategies to speed up a numerical impact analysis on structures are provided. A new principle to define the limit of low velocity impact is established.